2019
DOI: 10.14689/issn.2148-2624.1.7c.2s.8m
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Students on Central System Examinations in Turkey: A Metaphor Analysis Study

Abstract: Öz. Bu araştırmanın amacı, öğrencilerin Türkiye'deki merkezi sistem sınavları hakkındaki algılarını metafor analizi yolu ile incelemektir. Bu araştırmada, nitel araştırma desenlerinden biri olan, fenomenoloji araştırma deseni" kullanılmıştır. Araştırmanın katılımcılarını 2014-2015 eğitimöğretim yılında Niğde ilinde resmi fen, Anadolu ve mesleki ve teknik Anadolu liselerinde öğrenim görmekte olan öğrenciler (n = 372) oluşturmuştur. Araştırmada elde edilen veriler "Merkezi sistem sınavları (LYS, YGS, TEOG, SBS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The study by Şad and Şahiner (2016) focused on opinions of students, teachers, and parents about TEOG and showed that stronger sides of exam were right to enter exam in own school building, a make-up exam possibility, extending exam for two semesters, and not using correction-for-guessing formula whereas the criticized points were unsecure exam conditions, and promoting private course institutions and tutoring. A metaphor study was performed by Baş and Kıvılcım (2019) to check perceptions of students about central exams like SBS and TEOG. The authors found metaphors which can be grouped as "concept as anxiety, torture, disturbing thing", "concept as unfair, unnecessary race", "concept as unconventional, irrelevant, variable, or always existing thing", "concept as turning point of our lives", "concept of selective and determinative of life", and "concept as long or a short-term race".…”
Section: System Of Transition To Highmentioning
confidence: 99%
“…The study by Şad and Şahiner (2016) focused on opinions of students, teachers, and parents about TEOG and showed that stronger sides of exam were right to enter exam in own school building, a make-up exam possibility, extending exam for two semesters, and not using correction-for-guessing formula whereas the criticized points were unsecure exam conditions, and promoting private course institutions and tutoring. A metaphor study was performed by Baş and Kıvılcım (2019) to check perceptions of students about central exams like SBS and TEOG. The authors found metaphors which can be grouped as "concept as anxiety, torture, disturbing thing", "concept as unfair, unnecessary race", "concept as unconventional, irrelevant, variable, or always existing thing", "concept as turning point of our lives", "concept of selective and determinative of life", and "concept as long or a short-term race".…”
Section: System Of Transition To Highmentioning
confidence: 99%